Self-reported medication information needs among medication users in a general population aged 40 years and above - the Tromsø study - Mari J. Walquist; Kristian Svendsen; Beate H. Garcia; Trine S. Bergmo; Anne Elise Eggen; Kjell H. Halvorsen; Lars Småbrekke; Unni Ringberg; Elin C. Lehnbom; Marit Waaseth (BMC, 2022)
Abstract Purpose To determine the prevalence and associated factors of self-reported medication information needs among medication users in a general population aged 40 years and above - The Tromsø Study. Methods Cross-sectional study of medication users (n = 10,231) among participants in the Tromsø Study, a descriptive analysis of questionnaire data and multivariable logistic regression (n = 9,194). Results Sixteen percent of medication users expressed a need for more information about own medications. Overall, medication users agreed to a higher degree to have received information from the GP compared to the pharmacy. Concerned medication users and those disagreeing to have received information about side effects had the highest odds for needing more information (OR 5.07, 95% CI 4.43-5.81) and (OR 2.21, 95% CI 1.83-2.68), respectively. Medication users who used heart medications (e.g., nitroglycerin, antiarrhythmics, anticoagulants) (OR 1.71, 95% CI 1.46-2.01), medication for hypothyroidism (OR 1.36, 95% CI 1.13-1.64) or had moderately health anxiety had expressed need for medication information. Whereas medication users with lower education, those that never used internet to search for health advice, and medication users who disagreed to have received information about reason-for-use were associated with lower odds (OR 0.75, 95% CI 0.62-0.91), (OR 0.85, 95% CI 0.74-0.98) and (OR 0.68, 95% CI 0.53-0.88), respectively. Conclusion This study demonstrated that there is need for more information about own medications in a general population aged 40 years and above and shed light on several characteristics of medication users with expressed information need which is important when tailoring the right information to the right person.